Two orchestral embodimentsof three pieces from op. 54 by Edvard Grieg - Urniežius, Rytis (Muzikološki zbornik, 2020)
Lyric Suite is an orchestral version of four movements from Grieg's Lyric Pieces V, op. 54. Three out of these four movements exist in two orchestral versions. The aim of the current research is to highlight peculiar traits of Grieg's orchestral style in the late period of composer's life by comparing scores of two orchestrators.
Keywords: glasbene analize; Grieg, Edvard; Lirična suita; Lyric Suite; musical analysis; musicology; muzikologija; norveški skladatelji; Norwegian composers; orchestration; orkestracija